2003
DOI: 10.1128/mcb.23.18.6484-6493.2003
|View full text |Cite
|
Sign up to set email alerts
|

Highly Restricted Localization of RNA Polymerase II within a Locus Control Region of a Tissue-Specific Chromatin Domain

Abstract: RNA polymerase II (Pol II) can associate with regulatory elements far from promoters. For the murine ␤-globin locus, Pol II binds the ␤-globin locus control region (LCR) far upstream of the ␤-globin promoters, independent of recruitment to and activation of the ␤major promoter. We describe here an analysis of where Pol II resides within the LCR, how it is recruited to the LCR, and the functional consequences of recruitment. High-resolution analysis of the distribution of Pol II revealed that Pol II binding wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
73
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(83 citation statements)
references
References 66 publications
10
73
0
Order By: Relevance
“…Furthermore, our data reveal recruitment of polII to an enhancer far away from the core promoter. Similarly, it has been demonstrated that polII is recruited to the ␤-globin locus control region, and that this occupancy depends at least in part on the presence of GATA-1 (38). Further support for polII occupancy at enhancers has been described for the androgen-specific gene PSA and for the TCR-␤ locus, both supported by in vivo footprinting and ChIP experiments (reviewed in ref.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, our data reveal recruitment of polII to an enhancer far away from the core promoter. Similarly, it has been demonstrated that polII is recruited to the ␤-globin locus control region, and that this occupancy depends at least in part on the presence of GATA-1 (38). Further support for polII occupancy at enhancers has been described for the androgen-specific gene PSA and for the TCR-␤ locus, both supported by in vivo footprinting and ChIP experiments (reviewed in ref.…”
Section: Discussionmentioning
confidence: 75%
“…These are located in the region where the intergenic transcripts were perfectly preserved in memory Th2 cells (downstream of the CNS1 site), and thus this could account for the continuous generation of high level intergenic transcripts observed in the region. Similar highly restricted localization of Pol II within a locus control region was reported in the ␤-globin gene (53). As Pol II is known to associate with histone-modifying enzymes (26), Pol II localization within a locus control region may have also a specific role in histone modification, such as H3-K4 methylation and H3-K9/14 acetylation.…”
Section: Discussionmentioning
confidence: 59%
“…As the LCR is a site of intergenic transcription (47-50), LCR-associated Pol II might also generate functional transcripts and/or alter chromatin structure in a transcriptiondependent manner. However, blocking Pol II elongation has little to no effect on the ␤-globin locus histone modification pattern (50). GATA-1 increases Pol II occupancy at the LCR, although Pol II occupies the LCR in GATA-1-null cells (30).…”
Section: Hs2mentioning
confidence: 99%